Speech Function Analysis in Online Classroom - Ayu Indari; Tri Indah Rezeki; Rakhmat Wahyudin Sagala (Muhammadiyah University of Mataram, 2021)
The pandemic of Covid-19 has had an impact on education. Because of the presence of the corona virus, face-to-face teaching-learning activities have been hampered. One of them is the use of an online classroom in which teachers or lecturers engage verbally with students. The examination of speech function can reveal verbal interaction. The purpose of this research is to look at Speech Function in online Structure and Speaking programs. This study looks into: 1) speech function classification in online Structure and Speaking classes; 2) how speech function is implemented in online Structure and Speaking classes; and 3) why speech function is implemented in online Structure and Speaking classes. The data for this study was gathered through qualitative research from the discourse of lecturers and students in online Structure and Speaking classes. Content analysis and Speech Function analysis were used to examine the data. The speech function can be used to evaluate 32 utterances in the Structure online classroom. Statement has 56.3 percent, Question has 34.3 percent, Offer has 3.1 percent, and Command has 6.3 percent, according to the Structure class statistics. The data from the first question of the speech function of statement in the online speaking class is 100 percent accurate. It is because the inquiry is a form of experience-based self-opinion, and many claims require data to reinforce their answers. The second question is statement (67.8%), with command coming in second at 30.3%.